P-27THE EFFECTS OF CHRONIC ALCOHOL CONSUMPTION ON ADIPONECTIN AND INSULIN RESISTANCE. (September 2014) - Jeong, J. E.; Kwak, S. M.; Bang, S. H.; Lim, S. G.; Kim, D. J.
Abstract : The purpose of this study was to understand the effects of chronic alcohol consumption on diabetes. We used 14-week-old OLETF rats which have type 2 diabetes (T2DM) and non-diabetic control LETO rats. The rats were randomized into four groups. : (1) OLETF-Control(OC, n = 10), (2) OLETF-Alcohol (OE, n = 10), (3) LETO-Control (LC, n = 10), (4) LETO-Alcohol LE, n = 10). Rats in the alcohol-fed group were fed with a liquid alcohol diet over 10 week period. After each period of 5 week and 10 week feeding, we did Intraperitoneal Glucose Tolerance Testing (IP-GTT) and measured the blood adiponectin and insulin levels. The first IP-GTT data was not shown any significant difference between groups. After 10 weeks 30 minute-glucose levels of OE group is significantly higher than OC group. And after 90 minute, the glucose level of OE group was also significantly higher than OC group. The level of insulin was increased in OE group than OC group. (p < 0.05) The level of adiponectin in LE group and OE group was significantly lower than each control group. We suggest heavy alcohol consumption reduced the level of adiponectin which regulate insulin sensitivity. Reduced adiponectin level induced the insulin resistance which is one of the main factors of worsening T2DM in diabetic animal model.